PENERAPAN FLEKSIBILITAS HUKUM PADA PUTUSAN HAKIM DALAM PERKARA WARIS DI PENGADILAN AGAMA PALU - Mayyadah Mayyadah; Sapruddin Sapruddin (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
Flexibility in Islamic Law can be found in judges’ rulings in many cases of inheritance in religious court. Therefore, the judge as a law enforcer should make ijtihad based on principles of justice and maslahah. One of method of judges in deciding heirs is to consider about juridical, philosophical and sociological aspects, but can not ignore the facts of the trial. This study aims to analyze the implementation of legal flexibility in inheritance cases within religious court in Palu City, Central Sulawesi. The study found there are at least 3 cases that apply the islamic law flexibility theory. That cases number are 050/Pdt.G/2014/PA.Pal., 246/Pdt.G./2016/PA.Pal., and 562/Pdt.G/2014/PA.Pal.